Case report: hepatobronchial lymphatic communications in single ventricle patients as a pathophysiological mechanism of plastic bronchitis: diagnosis and treatment. Issue 6 (6th November 2020) - Rabinowitz, Deborah; Radtke, Wolfgang; Bhat, Majeed; Itkin, Maxim
Abstract: Background : Plastic bronchitis is a rare but devastating complication in single ventricle patients after Fontan completion. Recent advances in dynamic contrast-enhanced magnetic resonance lymphangiogram demonstrate the typical pathophysiological mechanism of the thoracic duct leaking lymphatic fluid towards the bronchi resulting in intraluminal casts. This has been termed abnormal pulmonary lymphatic perfusion and has been successfully treated in 94% of patients with thoracic duct occlusion. However, in some cases, this aberrant flow is not identified and therefore no intervention is available. This case report identifies a newly discovered origin of abnormal lymphatic flow from the liver to the bronchi and the treatment of these patients. Case summary : We report two cases of plastic bronchitis in single ventricle patients with no identified abnormal lymphatic pulmonary perfusion from the thoracic duct. Both patients underwent liver lymphangiogram and demonstrated aberrant flow from the hepatic lymphatic ducts to the bronchi. These were successfully occluded, and plastic bronchitis symptoms resolved in both cases. Discussion : The recent discovery of the abnormal pulmonary lymphatic perfusion from the thoracic duct to the bronchi has allowed successful treatment of 94% of single ventricle patients with plastic bronchitis. The discovery of hepatobronchial lymphatic perfusion reveals an occult aetiology of plastic bronchitis and a second target for embolization and successful treatment.